Sejarah Perkembangan Koperasi Syariah di Indonesia: Transformasi Koperasi dari Masa Ke Masa - Wildani Mukholid; Maslahah Maslahah; Lailatul Zannah; Feby Juan Hendrawan; Dwiki Muhammad Fadhillah; Gama Pratam (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
Compared to other Islamic financial institutions, Islamic cooperatives are one type of financial institution that is still less known in the community. This can be seen from the lack of familiarity of the term sharia cooperative to our society. This research is a qualitative research, in accordance with the object of study, this type of research is included in the category of library research, which is a systematic approach to collecting, analysing, and evaluating relevant information from various academic sources. By 2022, there were 3,912 active sharia savings and loan cooperatives (KSPPS) in Indonesia. This indicates a significant expansion in the number of Islamic cooperative institutions during this period when compared to the previous period, when there was a Covid-19.There needs to be an Islamic cooperative development strategy in Indonesia in order to optimise the role of Islamic cooperatives in improving the MSME sector in Indonesia.The element of need that is the main key in the development strategy of Islamic cooperatives in Indonesia to improve MSMEs is the need for strong support in the legal aspects of Islamic cooperatives (positive law and sharia law).